Reply to "Preparing Current and Future Practitioners to Integrate Research in Real Practice Settings" by Bruce A. Thyer. (July 2015) - Gambrill, Eileen
Professor Thyer addresses the vital question "How can we prepare practitioners to integrate research in practice settings?" His focus on ethical concerns due to a failure in integration and suggestion to seek legal remedies are welcome ones. Their importance is highlighted by continuing to disregard the close relationship between ethical and evidentiary concerns in everyday practice and policy.